STRATEGI DAKWAH MELALUI LAGU MATI MASUK SURGA - Ghifari, Irfan; Abdurrazaq, Muhammad N.; Tebba, Sudirman (Journal of Islamic Studies, 2023)
Da'wah is one of the obligatory tasks for every Muslim, especially in conveying good messages. One of the da'wah activities that is commonly found is through a lecture activity. During the Sunan Kalijaga era, preaching was not only through lecture activities, but through an art that was already being performed by the general public on the island of Java. With the development of the times, many methods of da'wah are used, one of which is through music. Wali Band is a band that preaches through music. Of the many songs that have been composed, the Wali Band song which is used as the object of research is "Mati Masuk Surga". The purpose of this research is to find out the background of the creation of the song "Mati Masuk Surga" and the Wali Band's missionary strategy in the future. In this study, the authors used a qualitative research approach. In collecting data, researchers used observation techniques, interviews, and documentation. For data analysis techniques used through data analysis, data reduction, data presentation, and drawing conclusions. After analyzing the song "Mati Masuk Surga", research found that the song was created because during the pandemic many people used the TikTok application to entertain themselves. The strategy carried out by Wali Band in the future uses a sentimental approach (Al-Manhaj Al-Lathifi).